Konsep Restorative Justice Dalam Penanganan Tindak Pidana Penganiayaan - Achmad Badawi; Supanto Supanto; Tika Andarasni Parwitasari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Criminal Law plays a crucial role in regulating the daily behavior of society, identifying actions that violate ethics and morals, and asserting that such actions can be considered crimes potentially harmful to others as legal subjects. Although assault is generally regulated in the Criminal Code as a violation of bodily integrity, there are differences in interpretation among legal experts regarding the meaning and concept of assault. The use of the judicial system to resolve cases does not always meet the expectations of perpetrators, victims, or the community in achieving justice. The emergence of the concept of Restorative Justice brings a new paradigm to the law enforcement system in Indonesia, aiming to be a holistic solution that considers the rights of both victims and perpetrators. Restorative Justice aims to restore the situation to its state before the criminal act, eliminate negative stigma, and avoid revenge. Thus, it is expected that the perpetrators can honestly admit their actions, take responsibility for their mistakes, and commit to improving themselves to avoid repeating their actions.